Economics and governance of vocational and professional education and training (including apprenticeship) : theoretical and empirical results for researchers and educational policy leaders - Backes-Gellner, Uschi [Herausgeber]; Renold, Ursula [Herausgeber]; Wolter, Stefan C. [Herausgeber] (hep Verl., 2020)
"This book provides an overview of selected research results on the economics and governance of Vocational and Professional Education and Training (VPET), particularly apprenticeship training. It compiles over 25 research articles published in leading peer-reviewed journals, places their results in a broader context - thereby making them accessible to practitioners - and refers to newer research that has not yet been published. All of this research covers the role and functions of the three most important actors in VPET: firms, individuals, and the state/institutional frameworks. Given that the decisions and interactions of these three players are critical for a successful VPET system, this book addresses both decision makers at all VPET levels and researchers interested in the economics and the management of VPET systems. Focusing on not only the dual VPET systems of Switzerland and Germany but also other VPET systems worldwide, the research presented here analyzes and discusses the preconditions involved in all three roles. The results lay a foundation for future VPET research and for VPET practitioner and policymaker decision-making in countries with existing VPET systems. These results also help to shape policy-making in countries that are about to start or have just begun to establish VPET systems and to create an agenda for establishing VPET research." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; S 4 Kosten & Finanzierung; G 2.3.4 Qualifikationswandel; Berufsbildungssystem; Governance; Berufsausbildung; Kosten; Betrieb; Ausbildungsverhalten; Höhere Berufsbildung; Durchlässigkeit im Bildungssystem; Arbeitskräftemobilität; Dequalifizierung; Lernen am Arbeitsplatz; Bundesrepublik Deutschland; Schweiz